2008
DOI: 10.1073/pnas.0710618105
|View full text |Cite
|
Sign up to set email alerts
|

SymRK defines a common genetic basis for plant root endosymbioses with arbuscular mycorrhiza fungi, rhizobia, and Frankia bacteria

Abstract: Root endosymbioses vitally contribute to plant nutrition and fitness worldwide. Nitrogen-fixing root nodulation, confined to four plant orders, encompasses two distinct types of associations, the interaction of legumes (Fabales) with rhizobia bacteria and actinorhizal symbioses, where the bacterial symbionts are actinomycetes of the genus Frankia. Although several genetic components of the host-symbiont interaction have been identified in legumes, the genetic basis of actinorhiza formation is unknown. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
178
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(190 citation statements)
references
References 35 publications
6
178
0
3
Order By: Relevance
“…For others, it is likely that their transcripts were not detected and have not been sequenced in one of the two actinorhizal species. For instance, this was the case of SymRK, whose symbiotic role has already been demonstrated in C. glauca (Gherbi et al, 2008) but was not present among C. glauca unigenes. Interestingly, expression analysis of these symbiosis homologs in A. glutinosa and C. glauca revealed that the accumulation of transcripts in nodules versus uninfected roots was not only comparable between the two actinorhizal species but also similar to those found in legumes (Fig.…”
Section: Validation Of Microarray Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…For others, it is likely that their transcripts were not detected and have not been sequenced in one of the two actinorhizal species. For instance, this was the case of SymRK, whose symbiotic role has already been demonstrated in C. glauca (Gherbi et al, 2008) but was not present among C. glauca unigenes. Interestingly, expression analysis of these symbiosis homologs in A. glutinosa and C. glauca revealed that the accumulation of transcripts in nodules versus uninfected roots was not only comparable between the two actinorhizal species but also similar to those found in legumes (Fig.…”
Section: Validation Of Microarray Resultsmentioning
confidence: 89%
“…Complete descriptions of BLAST results and related references are given in Supplemental Tables S5 and S6. * DMI2/SymRK was not found in the C. glauca unigene database, and expression results of Gherbi et al (2008) were used for comparison with A. glutinosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This task is (still) difficult because of the lack of genomics and genetics tools, but rewarding when the outcome proves some long-standing assumptions and suggests new ways to address old questions. A nice example is the work of Gherbi et al (1) presented in this issue of PNAS. Their article deals with a nonmodel plant, Casuarina glauca, whose roots interact with both symbiotic fungi and nitrogen-fixing bacteria, and evidences the central and ancestral role of the plant receptor SYMRK in the establishment of the three major types of root endosymbioses.…”
mentioning
confidence: 99%